Five-Year Outcomes of Transfemoral Transcatheter Aortic Valve Replacement or Surgical Aortic Valve Replacement in a Real World Population Final Results From the OBSERVANT Study - Barbanti M; Tamburino C; D'Errigo P; Biancari F; Ranucci M; Rosato S; Santoro G; Fusco D; Seccareccia F; and for the OBSERVANT Research Group (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Background: The OBSERVANT study (Observational Study of Effectiveness of SAVR-TAVI Procedures for Severe Aortic Stenosis Treatment) showed that mortality at 1 year is similar after transfemoral transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (SAVR) for real-world propensity-matched patients with aortic stenosis at low and intermediate risk. We report the 5-year outcomes of the Italian OBSERVANT study. Methods and Results: The unadjusted enrolled population (N=7618) between December 2010 and June 2012 included 5707 patients on SAVR and 1911 patients on TAVR. The propensity score method was applied to select 2 groups with similar baseline characteristics. All outcomes were adjudicated through a linkage with administrative databases. The primary end points of this analysis were death from any cause and major adverse cardiac and cerebrovascular events at 5 years. The matched population had a total of 1300 patients (650 per group). The propensity score method generated a low and intermediate-risk population (mean logistic EuroSCORE 2: 5.1 +/- 6.2% versus 4.9 +/- 5.1%, SAVR versus transfemoral TAVR; P=0.485). At 5 years, the rate of 5 death from any cause was 35.8% in the surgical group and 48.3% in the transcatheter group (hazard ratio, 1.38; 95% CI, 1.12-1.69; P=0.002). Similarly, TAVR was associated with an increased risk of major adverse cardiac and cerebrovascular events as compared with SAVR (42.5% versus 54.0%; hazard ratio, 1.35; 95% CI, 1.11-1.63; P=0.003). The cumulative incidence of cerebrovascular events, myocardial infarction, and coronary revascularization were similar in the study groups at 5 years. Conclusions: The present results suggest that at 5 years, in a real-world population with severe aortic stenosis and at low and intermediate risk, suggest that SAVR is associated in with lower mortality and major adverse cardiac and cerebrovascular events rates than transfemoral TAVR performed using first-generation devices. These data need to be confirmed in randomized trials using new-generation TAVR devices.